Pengaruh Media Sosial Terhadap Omzet Penjualan Smartphone di Toko D1one Acc Medan - Ayyub Ramadhan; Muhammad Ikhsan Harahap (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
This study aims to determine the effect of social media on sales turnover at the D1one Acc Medan Store. This study uses an explanatory quantitative research approach using surveys as a means of data collection which aims to find out how one variable affects other variables. The population in this study were all employees and shop visitors with a total of 527 people. The sampling method used a non-probability sampling method, namely saturated sampling because it took samples from the entire population, using a Likert scale, this research is a survey research where primary data is collected through questionnaires, secondary data is collected from smartphone outlets and literature studies. The data analysis method used is descriptive analysis method with simple linear regression analysis technique Crosstab as a tool to calculate whether there is a relationship or influence between social media on sales turnover. The results of the hypothesis in this study prove that social media has a positive and significant effect on sales turnover where the t count is 6.708, which is greater than the t table of 1.990. From Adjusted R Square = 0.352, it can be said that the change in the dependent variable (Y) is 35.2% to the X variable, while the remaining 64.8% is caused by other factors not found in the study.